IMPLEMENTASI COMPLIANCE RISK MANAGEMENT SEBAGAI DECISION SUPPORT SYSTEM DALAM KEGIATAN PENAGIHAN DI DIREKTORAT JENDERAL PAJAK - Halida An Nabila; Primandita Fitriandi (Politeknik Keuangan Negara STAN, 2021)
This study aims to analyze the implementation of Compliance Risk Management (CRM) as a decision support system for tax collection purpose at Directorate General of Taxes. This study evaluates the implementation of CRM for tax collection purpose using the usability inquiry to evaluate CRM through questionnaire, observation, and interview. The usability score is obtained from the questionnaire, reflecting the level of usability of CRM as a decision support system in determining priority taxpayers for tax collection action. The validity of the score is then confirmed and deepened by field observations and interviews. Based on the research results, the role of CRM in determining priority for tax collection action is nothing more than a trigger instead of a decision support system it was expected to be. This is due to several shortcomings it poses in terms of effectiveness, efficiency, and accuracy which are mainly caused by slow data update. However, CRM is adequate in terms of understandability, operability, and learnability.